2004
DOI: 10.1088/0953-8984/16/29/008
|View full text |Cite
|
Sign up to set email alerts
|

Coverage dependence of the dynamics of ethylene adsorption on Ag(210)

Abstract: The sticking probability of C 2 H 4 on Ag (210) is studied by the molecular beam technique and by high resolution electron energy loss spectroscopy. At a crystal temperature of 110 K, adsorption occurs initially into a stable, π-bonded, state. At larger coverage a metastable state is populated, too. The sticking probability, S, decreases with increasing translational energy indicating nonactivated adsorption. At low coverage and for impact angles from −60• to +60• , S is angle independent, decreasing only as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Outcomes (2) and (3) are expected and have been reported already, e.g., for C 2 H 4 /Ag(410) and C 2 H 4 /Ag(210) . In particular, outcome (2) indicates that an extrinsic precursor is active both at thermal and hyperthermal energy.…”
Section: Resultssupporting
confidence: 72%
“…Outcomes (2) and (3) are expected and have been reported already, e.g., for C 2 H 4 /Ag(410) and C 2 H 4 /Ag(210) . In particular, outcome (2) indicates that an extrinsic precursor is active both at thermal and hyperthermal energy.…”
Section: Resultssupporting
confidence: 72%
“…Data taken from Refs. [422,423]. has been developing rapidly in the last years, so that we did not pretend to cover the whole subject.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of steps significantly enhances the total coverage of chemisorbed ethylene which can be achieved on the surface under UHV conditions: while for Ag(100) Θ ≈ 0.07 ML even when dosing at high translational energy [421], for Ag (410) and Ag(210) a maximum coverage of ≈0.12 ML was attained [422,423]. The fact that a similar coverage is reached for the two stepped surfaces and that its value corresponds to half the nominal density of steps on Ag (410) indicates that sites at adjacent steps cannot be occupied for Ag (210).…”
Section: Dissociative Chemisorption: Methane On Stepped Pt and Ni Surmentioning
confidence: 99%
“…Studies of C 2 H 4 adsorption on Ag(210) and Ag(410), based on supersonic molecular beam technique, have demonstrated that the sticking probability, measured with the King and Wells technique, is increased on stepped surfaces compared to flat surface, while the achievable maximum coverage is rather independent of the density of steps. 4,5 In this paper, we present the results of the experimental and computational investigation on adsorption of ethylene on Cu(410) and compare them to those obtained on other Cu single crystal surfaces, for example, Cu(210), 6 in order to discuss the effect of step sites on reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…As for the hydrogenolysis of cyclohexane, a surface with narrower terrace has better reactivity, although the methane dissociation is catalyzed better by a surface with wider terrace. Studies of C 2 H 4 adsorption on Ag(210) and Ag(410), based on supersonic molecular beam technique, have demonstrated that the sticking probability, measured with the King and Wells technique, is increased on stepped surfaces compared to flat surface, while the achievable maximum coverage is rather independent of the density of steps. , …”
Section: Introductionmentioning
confidence: 99%